2005
DOI: 10.2320/matertrans.46.2386
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Reaction and Mechanical Characterization of Eutectic Sn–Zn/ENIG Solder Joints during Reflow and Aging

Abstract: The interfacial reactions and joint reliabilities between Sn-9 mass%Zn solder and an electroless nickel-immersion gold (ENIG) plated Cu substrate were investigated during reflow and isothermal aging at temperatures between 343 and 423 K for aging times of up to 2400 h. After reflowing and aging, the intermetallic compound (IMC) formed at the interface was found to be AuZn 3 . No Ni-containing reaction products, such as Ni-Zn, Ni-Sn and Ni 3 P, were observed to form at the interface. The interfacial microstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Most interestingly, there was no P-rich Ni compound observed at the resolution limit of the SEM used. The absence of P-rich Ni layer at the interface of the Sn-Zn solder/Ni(P) system was also confirmed by other researchers [15,18]. The average thickness of intermetallic layers was 0.8-1.2 m. In the initial reflow condition, the IMCs on the Ni(P) metallization were mainly composed of Au-Ni-Sn-Zn.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Most interestingly, there was no P-rich Ni compound observed at the resolution limit of the SEM used. The absence of P-rich Ni layer at the interface of the Sn-Zn solder/Ni(P) system was also confirmed by other researchers [15,18]. The average thickness of intermetallic layers was 0.8-1.2 m. In the initial reflow condition, the IMCs on the Ni(P) metallization were mainly composed of Au-Ni-Sn-Zn.…”
Section: Resultssupporting
confidence: 77%
“…It is consistent with the high value of their shear strengths. Yoon et al also observed no deterioration of the joint strength of the Sn-Zn solder/Ni(P) system even after 120 min of reflow [15]. Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Consequently, the results of interfacial reaction and shear test showed that the Sn-9Zn/Cu solder joint has an undesirable joint reliability. Recently, we have also investigated the interfacial reactions and mechanical properties of the Sn-9Zn/ENIG plated Cu joints during isothermal aging, and the results are reported elsewhere [22]. According to the result, during the reflow process, Au did not dissolve into the solder and AuZn 3 IMC layer formed by the fast reaction of Au and Zn.…”
Section: Resultsmentioning
confidence: 77%
“…Moreover, it was also reported that a Au-Zn-Ni-Sn intermetallic compound was present at the joint interface between Sn-9Zn and the Ni-P/Au plating layer. 22,27 According to a study of a Sn-3Ag-0.5Cu BGA ball attached to a Ni-P/Au pad using a Sn-8Zn-3Bi solder paste, the reflow temperature, and perhaps time, had a significant effect on the type of interfacial intermetallic compound formed. 23 Specifically, a low peak reflow temperature of 210°C gave a predominantly Au-Zn layer, but when applying a high reflow condition with a peak temperature of 240°C, an interfacial Ni-Sn-Cu-Zn layer appeared instead of Au-Zn intermetallics.…”
Section: Cross-sectional Analyses Of Interfacial Microstructurementioning
confidence: 99%
“…In previous studies of soldering systems of the Sn-Zn family with the ENIG surface finish, formation of fine Zn-containing intermetallic compounds was observed at the joint interfaces. [20][21][22][23][24][25][26][27] This indicates that the intervention of Zn in the interfacial reaction proceeds in this soldering system. Therefore, from the aspect of controlling the interfacial reaction, addition of a Zn compound to the flux should demonstrate interesting behavior at the joint interface when soldering on a Ni-P/Au plating layer.…”
Section: Introductionmentioning
confidence: 99%